Association Between Cholinesterase Inhibitors and New-Onset Heart Failure in Patients With Alzheimer's Disease: A Nationwide Propensity Score Matching Study - Hsieh, Ming-Jer; Chen, Dong-Yi; Lee, Cheng-Hung; Wu, Chia-Ling; Chen, Ying-Jen; Huang, Yu-Tung; Chang, Shang-Hung (Frontiers in cardiovascular medicine, 2022)
Autonomic nervous dysfunction is a shared clinical feature in Alzheimer's disease (AD) and heart failure (HF). Cholinesterase inhibitors (ChEIs) are widely used autonomic modulators in patients with AD, but their primary preventive benefit on new-onset HF is still uncertain. This study examined whether ChEIs have a primary preventive effect on new-onset HF in patients with AD. This propensity score matching (PSM) study was conducted using data from the National Health Insurance Research Database of Taiwan for 1995 to 2017. Certificated patients with AD and without a history of HF were divided into ChEI (donepezil, rivastigmine, or galantamine) users or nonusers. The primary endpoint was new-onset HF, and the secondary endpoints were myocardial infarction and cardiovascular death after 10-year follow-up. After screening 16,042 patients, 7,411 patients were enrolled, of whom 668 were ChEI users and 1,336 were nonusers after 1:2 PSM. Compared with nonusers, ChEI users exhibited a significantly lower incidence of new-onset HF (HR 0.48; 95% CI 0.34-0.68, p < 0.001) and cardiovascular death (HR 0.55; 95% CI 0.37-0.82, p = 0.003) but not of myocardial infarction (HR 1.09; 95% CI 0.52-1.62, p = 0.821) after 10-year follow-up. The preventive benefit of ChEI use compared with Non-use (controls) was consistent across all exploratory subgroups without statistically significant treatment-by-subgroup interactions. Prescription of ChEIs may provide a preventive benefit associated with lower incidence of new-onset HF in patients with AD after 10-year follow-up.